The Secret of the Hidden Room - Thomas, Jerry D.; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 1999)
When his baseball flies into the window of the old house next to the ball field, Sammy joins the other Shoebox Kids in investigating the mystery of the house and making some discoveries about prejudice.
Keywords: Story Collection